2019
DOI: 10.3233/wor-192921
|View full text |Cite
|
Sign up to set email alerts
|

World Trade Center: A longitudinal case study for treating Post Traumatic Stress Disorder with Emotional Freedom Technique and Eye Movement Desensitization and Reprocessing

Abstract: BACKGROUND: Emotional Freedom Techniques (EFT) and Eye Movement Desensitization and Reprocessing (EMDR) have been empirically validated as effective psychotherapeutic interventions for treating Post Traumatic Stress Disorder (PTSD). This single subject design case study is of a survivor of the Twin Towers collapse who was treated for prolonged PTSD complicated by dissociated memories. OBJECTIVE: EMDR and EFT's effectiveness in treating PTSD were evaluated. METHOD: Multiple assessments using Trauma Symptom Inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
2
0
1
Order By: Relevance
“…The results of the current study demonstrated that the training in Emotional Freedom Technique led to a reduction in the symptoms of Post-Traumatic Stress Disorder (PTSD) following emotional trauma in women affected by marital infidelity. No study directly corresponding to the present research focused on PTSD symptoms in women affected by infidelity was found; however, this study aligns with the previous findings (Akbari et al, 2023;Alamdar Baghini et al, 2021;Church, 2014;Church et al, 2016;Church et al, 2018;Church et al, 2017;Clond, 2016;Dincer & Inangil, 2021;Gaesser, 2020;Minewiser et al, 2016;Nicosia et al, 2019;Sebastian & Nelms, 2017;Study, 2017;Yavari Kermani et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the current study demonstrated that the training in Emotional Freedom Technique led to a reduction in the symptoms of Post-Traumatic Stress Disorder (PTSD) following emotional trauma in women affected by marital infidelity. No study directly corresponding to the present research focused on PTSD symptoms in women affected by infidelity was found; however, this study aligns with the previous findings (Akbari et al, 2023;Alamdar Baghini et al, 2021;Church, 2014;Church et al, 2016;Church et al, 2018;Church et al, 2017;Clond, 2016;Dincer & Inangil, 2021;Gaesser, 2020;Minewiser et al, 2016;Nicosia et al, 2019;Sebastian & Nelms, 2017;Study, 2017;Yavari Kermani et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…All of the 17 EFT [47,54,58,[64][65][66][67][68][76][77][78][79]87,[98][99][100][101] studies in this review reported impact on key outcomes, including PTSD symptom reduction, with no adverse effects reported. With 9/17 papers on EFT focused on war veterans, the majority of the research was generated by one organisation in the USA [64].…”
Section: Touch-based Interventions Being Utilised In the Treatment Of...mentioning
confidence: 99%
“…Based on the DSM-IV criteria for diagnosing and identifying the associated symptoms of PTSD (Table 1), the PCL was utilised in both civilian (PCL-C) and military (PCL-M) forms. Nine studies included other validated instruments of self-assessed PTSD based on the DSM VI [28,50,52,55,59,61,62,72,101]. Three studies did not utilise a validated tool to measure PTSD symptoms; these were qualitative [74] or descriptive papers in design [64,73].…”
Section: Touch-based Interventions Can Reduce the Symptoms Of Ptsdmentioning
confidence: 99%
“…Kalla, et al (2017) (8) EFT efektif mengatasi masalah emosional pada penyakit kronis dan serta untuk mendukung kesehatan secara fisik Nicosiaet al (2018) (9) Kombinasi EFT dan Eye Movement Desensitization and Reprocessing yang diberikan kepada pasien Post Traumatic Stress Disorder (PTSD) sangat efektif dan memungkinkan pasien untuk kembali bekerja setelah bertahun-tahun cacat.…”
Section: Hasilunclassified